Roles of school leaders in the management of emergencies caused by natural disasters in Gaborone, Botswana - Siphokazi Kwatubana; Vivian Molaodi (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
As natural disasters are becoming more frequent globally, understanding the role of school leaders during such disasters becomes more critical than ever, as they can grind schools to a halt. The fact that some communicable diseases such as COVID-19 are now classified as natural disasters means that natural disasters are increasing. The purpose of this study was to examine the role of school leaders in the management of emergencies caused by natural disasters. The study employed qualitative methods with three data collection tools to collect data from 20 participants – teachers, non-teaching staff members, and principals. The participants were purposively selected from schools in Gaborone, Botswana. The findings of this study reveal participants' understanding of the role of school leaders in all three stages of emergency management: before, during, and after an emergency because of previous experiences of natural disasters. The findings further suggest that school managers in emergency management play such roles as crisis managers, disaster managers, and caring and supportive leaders.